1999
DOI: 10.1080/01140671.1999.9514109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation and sowing date on phenology and yield of pinto beans(Phaseolus vulgarisL.) in Canterbury, New Zealand

Abstract: The phenology, yield, and yield components of pinto beans (Phaseolus vulgaris L.) were examined in the 1994/95 and 1995/96 growing seasons in Canterbury, New Zealand. In the first season, irrigation treatments (nil and full) combined with two sowing dates (27 October and 24 November) were studied. In 1995/96, pinto beans were sown on four dates (1, 15, 29 November and 13 December) with or without irrigation. Temperature was about average during the two seasons, but they were drier (50 and 60% of the long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Summerfield & These results provide valuable new information for modelling chickpea growth and development in cooltemperate subhumid climates. Simulation models of lentil (McKenzie et al 1994) and pinto bean (Phaseolus vulgaris L., Dapaah et al 1999) growth and development have shown various responses to temperature and photoperiod. The lack of response to photoperiod shown in the present work with these chickpea cultivars indicates that simulation modellers will need to use appropriate equations when modelling all stages, but e-f in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Summerfield & These results provide valuable new information for modelling chickpea growth and development in cooltemperate subhumid climates. Simulation models of lentil (McKenzie et al 1994) and pinto bean (Phaseolus vulgaris L., Dapaah et al 1999) growth and development have shown various responses to temperature and photoperiod. The lack of response to photoperiod shown in the present work with these chickpea cultivars indicates that simulation modellers will need to use appropriate equations when modelling all stages, but e-f in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, limited water availability (i.e., soil moisture levels) due to high levels of evaporation also negatively impacts yield components [10], fresh pod [7,9] or grain yields [8,99]. The detrimental effects of prolonged water deficit stress were also recorded in the studies of Dapaah et al [100,101] and Love et al [102], where common bean plants were exposed to no irrigation during the whole cultivation period. Conversely, excess application of water, i.e., to levels above the plant requirement, also limits yield [95] and introduces favourable conditions for disease proliferation, such as that of white mould [103].…”
Section: Irrigationmentioning
confidence: 96%
“…Plots with 50 plants m -2 had the highest mean number of pods plant -1 (13.42) and 400 plants m -2 , the least (3.37), a drop of 75%. Dapaah et al, [24] found that a low plant population of pinto beans (Phaseolus vulgaris) gave more pods plant -1 in a November sowing in Canterbury. The reduction in pods plant -1 at high density was due to increased interplant competition.…”
Section: Discussionmentioning
confidence: 99%